A evolução da ocupação urbana em zona de interesse social em Maringá-PR - Capellari, Mariandi Barcos (2012)
This paper seeks to understand which evolution of urban occupation in the area to be created exclusively for residential use for the working population in the city of Maringa, especially in Zone 06 and Conjunto Planalto, formulated as the principle area of social interest, so that which we understand the constraints that are involved or not recovery area. The objective of the study is to establish diagnosis and analyze an experience of social housing on the neighborhood in which it operates, so it can be replicated and contribute to enhancing the experiences record. In this research the urban plans are characterized that prevailed during the period of formation of the city to the current plan of 2006, the concept about terms that give understanding about how value is added to urban land for further analysis of economic valuation area study, the components that structure the neighborhood such as access to infrastructure, urban services and private key as well as an analysis of modifications and changes made to the site of the research, the Conjunto Planalto characterized by set through the pre building typologies -established in its implementation. This is a case study in which the intrinsic characterization of the site of research and the process of urban occupation is based on exploratory research, based on semi-structured interview and presentation of maps and town planning legislation based on work, among others. It appears that urban development along the deployment of Maringá, comes interfering in order to direct the recovery and consolidation of residential areas as well as the issue facing the areas of interest with demand for social housing.